Educação patrimonial e EJA: instrumento para a discussão sobre memória e patrimônio cultural - Cavalcanti, Marco Alexandre Nonato (2016)
This paper refers to a master's research which approached the heritage analysis as a cultural representation, a symbolic construction that evoke collective and social memories to assert peoples identities, a study of critical matrix analyzing the dispute among social classes throughout history. To accomplish this, there was a bibliographical research on cultural heritage and memory in which there was a reflection on the significant concept in context of heritage and disputes memories, observed as conflicts and social struggles. Continuing the theoretical study, an approach to a territory was carried out, touching upon the social, cultural and economy of the site, noting the evidence of history - memory of that space, redefining the concept of dispute memories and consequently the lack of recognition of certain groups in heritage goods. In this axis of the research, a document analysis was carried out about the cultural heritage of the territory under study, in a reflection aligned to nationwide documents and the subject under observation. As a condition to elucidate possibilities of overcoming this situation, a research approaches a concept of heritage education and while documentary study approaches the proposed curriculum EJA history mode of São Bernardo do Campo - SP, observing the limits and the possibilities of history study in the perspective of individual and collective memory. In this context, the study aims to analyze the organizational disputes and treatment of collective memories in a territory through the analysis of cultural heritage, observing the forces of power, moreover, it proposes a reflection on Heritage Education, as the possibility of resistance to hegemonic forces of group´s memory statement, in the perspective of provoking thought for fights and affirmation of collective identities